César Vallejo and Lee Kuei-Shien, poets of the love for the land and the social commitment - Jui-Ling, Chien (Espergesia, 2018)
César Vallejo is one of the most recognized Peruvian poets in the world due to the impressive innovation that his work entailed for the poetry of the twentieth century. Lee Kuei-shien introduced him to Taiwanese readers, being the first poet who translates Vallejo’s poems into Chinese Mandarin. In this way, and thanks to the fact that poetry has communicating vessels with the whole world, Taiwan and Perú are connected and are uniting Latin America and East Asia. Through poetry, the writers César Vallejo and Lee Kuei-shien reveal the value of the human being and the soul of their people. Given the importance of these aspects, in the present work we analyze and interpret the main ideas involved in the poetic work of both authors, focusing on the local and the social aspects of their poems. We also observed that the two poets seek to turn the word into a real capable force of influencing the destinies of the suffering humanity.